Recent Advances in Coatings of Implant and Dental Biomaterials - Park, Jun-Beom (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Knowledge, new concepts, and theoretical and experimental studies on coatings of implant and bone surfaces have been explained. Recent advancements in coating methods and materials for surface coating have both been extensively shown. Research on the use of modified implants and bone can be viewed through this paper. Improved understanding of the processes underpinning greater functionality will result from this issue.